The effect of crack path on tearing resistance of a narrow-gap Alloy 52 dissimilar metal weld. (1st October 2018) - Lindqvist, Sebastian; Sarikka, Teemu; Ahonen, Matias; Hänninen, Hannu
Highlights: HAZ cracks can deviate from the initial crack growth plane to the fusion boundary. The J-R curves are smallest for cracks initiating at the fusion boundary. The 10 × 10 and 10 × 20 SE(B) specimens yield similar J-R curves. Abstract: Fracture mechanical testing of welds with strength mismatch can lead to deviation of the crack path from the initial crack growth plane. Current fracture mechanics standards do not give guidance for analyses of the effect of crack path on the tearing resistance. In this study, the effect of crack path on tearing resistance was investigated by fracture mechanical testing and crack path analyses of a narrow-gap Alloy 52 dissimilar metal weld. The results show that tearing resistance of HAZ cracks deviating towards the same zone close to the fusion boundary is larger for cracks initially further from the fusion boundary. The results were obtained for a specific dissimilar metal weld, but the results can also be used to interpret the effect of crack path on tearing resistance in other type of welds.